Garlic Powder Supplementation Improves Growth, Nonspecific Immunity, Antioxidant Capacity, and Intestinal Flora of Chinese Mitten Crabs (Eriocheir sinensis). (7th November 2022) - Zhou, Ruoyu; Liu, Jinsong; Shi, Xueyan; Fu, Chunsheng; Jiang, Ying; Zhang, Ruiqiang; Wu, Yanping; Yang, Caimei
Abstract : This study was conducted to survey the effects of garlic powder on growth performance, nonspecific immunity, antioxidant capacity, and intestinal flora structure of Chinese mitten crabs. Altogether, 216 crabs which originally weigh 20.71 ± 0.13   g were randomly allocated into three treatment groups with 6 replicates of 12 crabs per replicate. The control group (CN) was fed a basal diet, while the other two groups were fed the basal diet supplemented with 1000 mg/kg (GP1000) and 2000 mg/kg (GP2000) garlic powder, respectively. This trial lasted 8 weeks. The results showed that the supplementation of garlic powder improved the final body weight, weight gain rate, and specific growth rate of the crabs (P < 0.05 ). Meanwhile, in serum, better nonspecific immune was confirmed by the enhancement of phenoloxidase and lysozyme levels, with the improvement of phosphatase activities in GP1000 and GP2000 (P < 0.05 ). On the other hand, the levels of total antioxidant capacity, glutathione peroxidases, and total superoxide dismutase in serum and hepatopancreas were increased (P < 0.05 ) while malondialdehyde content declined (P < 0.05 ) as the garlic powder was added to the basal diet. And, catalase in serum also shows an increase (P < 0.05 ). In both GP1000 and GP2000, genes related to antioxidant and immunity, for instance, Toll-like receptor 1, glutathione peroxidase, catalase, myeloid differentiation factor 88, TuBe, Dif, relish, crustins, antilipopolysaccharide factor, lysozyme, and prophenoloxidase mRNA expression levels, were increased (P < 0.05 ). The abundance of Rhizobium and Rhodobacter was reduced by adding garlic powder (P < 0.05 ). This study indicated that dietary addition of garlic powder promoted growth, enhanced nonspecific immunity and antioxidant capacity, activated Toll pathway, IMD pathway, and proPO system, increased antimicrobial peptide expression, while simultaneously improving the intestinal flora of Chinese mitten crabs.